2014
DOI: 10.4103/0019-509x.151984
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and prognosis of acute kidney injury following transarterial chemoembolization in patients with hepatocellular carcinoma: A prospective cohort study

Abstract: The present study showed that the incidence of post-TACE AKI was high in HCC patients (i.e., 7.59-21.84%) depending on criteria used. HGB (<120 g/L), serum TB (>13.5), and aminotransferase level (>55 U/L), age (>55 years) and post-TACE AKI history may be predictors of post-TACE AKI in HCC patients. The development of post-TACE AKI was associated with the risk of renal replacement treatment, prolonged renal insufficiency, or mortality according to AKIN criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…AKI is a common complication found after TACE in patients with HCC, and patients with post-TACE AKI have a higher risk of developing complications such as progression to CKD, ESRD, and death[ 200 - 204 ]. Preoperative CTP score, age, proteinuria, hemoglobin, serum total bilirubin, serum uric acid, aminotransferase level, post-TACE gastrointestinal bleeding, and previous post-TACE AKI history have been reported to be predictors of post-TACE AKI in HCC patients[ 201 , 205 , 206 ].…”
Section: Challenges Of Treating Hcc In Patients With Renal Dysfunctionmentioning
confidence: 99%
“…AKI is a common complication found after TACE in patients with HCC, and patients with post-TACE AKI have a higher risk of developing complications such as progression to CKD, ESRD, and death[ 200 - 204 ]. Preoperative CTP score, age, proteinuria, hemoglobin, serum total bilirubin, serum uric acid, aminotransferase level, post-TACE gastrointestinal bleeding, and previous post-TACE AKI history have been reported to be predictors of post-TACE AKI in HCC patients[ 201 , 205 , 206 ].…”
Section: Challenges Of Treating Hcc In Patients With Renal Dysfunctionmentioning
confidence: 99%
“…The patients treated with TACE are considered as a high risk group of AKI development. The incidence rate of AKI development after TACE was 9.1-23.8% [17][18][19][20]. Because the angiography using contrast media is conducted during TACE, contrast induced AKI develops after TACE.…”
Section: Discussionmentioning
confidence: 99%
“…25 The incidence of CI-AKI increases with age, preexisting renal disease, diabetic nephropathy, simultaneous use of nephrotoxic drugs, hemodynamic instability, anemia, and other causes of reduced renal function. 30,34 We performed a stratified analysis based on confounding variables [age, gender, renal function, hypertension, diabetes mellitus, shock, coronary artery disease, LVEF, Hb, RCDW (red cell distribution width), NLR (neutrophil to lymphocyte ratio), INR (international normalized ratio), eGFR (the estimated glomerular filtration rate), ALB (albumin), sCr, and UA(uric acid)] to investigate potential sources of statistical heterogeneity in the study and to assess the stability of bilirubin on outcome. In all selected studies, no data related to the use of contrast agents were provided for confounding factor analysis, only for other confounding factors such as age and gender.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…The seven points of the square visible in the funnel chart indicated that four studies with effect sizes need to be included in the future. The included studies need to be matched with the results of the Huang, 31 Hao, 30 Yao, 25 and Wu 11 studies to eliminate publication bias.…”
Section: Publication Biasmentioning
confidence: 99%